High-sensitivity C-reactive protein as biomarker of inflammation in children with asthma and allergic rhinitis - Dragana Malčić-Zanić; Olivera Ljuboja; Gordana Bukara-Radujković; Snežana Petrović-Tepić (Биомедицинска истраживања, 2018)
Introduction: Recent researches have shown that a high-sensitivity C-reactive protein (hs-CRP) can be the marker of chronic inflammation. The aim of the study is to investigate whether the serum hs-CRP concentration can be used as biomarker of inflammation in children with acute asthma attack and allergic rhinitis, as well as whether the monitoring of hs-CRP concentration can be an indicator of therapy success in children suffering from asthma. Methods: The study included 60 patients (30 of them with asthma and 30 with allergic rhinitis), both sexes, aged 7 to 14 years. Apart from being questioned about personal and family history, all patients underwent lung function and serum hs-CRP tests. The concentration of hs-CRP was measured by the latex particle immunoturbidimetric assay. In the group of children with asthma, measuring was performed before and three days after the therapy. Results: Patients with asthma had statistically significant higher levels of allergic sensitization, other associated allergic diseases, higher serum IgE concentrations, and lower levels of lung functions compared with those with allergic rhinitis. The values of hs-CRP (0.43 mg/l) were significantly higher in asthma patients than in those with allergic rhinitis (0.21 mg/l) (p= 0.002). 26.67% of patients with asthma had the hs-CRP values above the reference range, while all patients with allergic rhinitis had hs-CRP in the reference range. After a three-day therapy, the hs-CRP values were still maintained above the reference interval in four patients with asthma (13.33%) Conclusion: The research has showed that hs-CRP can be used as a biomarker of acute allergic inflammation in children with asthma and thus be a therapeutic response indicator.
Keywords: children; asthma; allergic rhinitis; hs-CRP